Role of Plant-Derived Natural Compounds in Experimental Autoimmune Encephalomyelitis: A Review of the Treatment Potential and Development Strategy - Yu-Xin Guo; Yuan Zhang; Yu-Han Gao; Si-Ying Deng; Li-Mei Wang; Cui-Qin Li; Xing Li (Frontiers Media S.A., 2021)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system that is mainly mediated by pathological T-cells. Experimental autoimmune encephalomyelitis (EAE) is a well-known animal model of MS that is used to study the underlying mechanism and offers a theoretical basis for developing a novel therapy for MS. Good therapeutic effects have been observed after the administration of natural compounds and their derivatives as treatments for EAE. However, there has been a severe lag in the research and development of drug mechanisms related to MS. This review examines natural products that have the potential to effectively treat MS. The relevant data were consulted in order to elucidate the regulated mechanisms acting upon EAE by the flavonoids, glycosides, and triterpenoids derived from natural products. In addition, novel technologies such as network pharmacology, molecular docking, and high-throughput screening have been gradually applied in natural product development. The information provided herein can help improve targeting and timeliness for determining the specific mechanisms involved in natural medicine treatment and lay a foundation for further study.